Sandy soil foundation temporary traffic road laying method based on high-strength polyethylene material
By laying high-strength polyethylene plates on the sandy foundation and carrying out reinforcement treatment, the shortcomings of traditional sandy foundation temporary roads in vehicle traffic and erosion resistance are solved, and higher mechanical properties and durability are achieved.
Patent Information
- Application Number
- CN202411645151.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional sand-based temporary roads have problems of deformation and insufficient anti-shrinkage ability in terms of vehicle traffic, especially when it is easily damaged under rainfall or water flow.
The plates prepared with high-strength polyethylene materials are statically pressed and vibratingly compacted by a vibrating roller, and steel pipes are drilled into the sandy foundation to reinforce them. Finally, high-strength polyethylene plates are laid on the surface of the sandy foundation.
It improves the mechanical properties, wear resistance and light resistance of sandy soil foundations, enhances the stability and erosion resistance of the road, and extends the service life of the road.
Smart Images

Figure BDA0005139519450000111 
Figure BDA0005139519450000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of civil engineering, in particular to a method for paving a temporary road open to traffic on a sandy soil foundation based on a high-strength polyethylene material. Background Art
[0002] Sandy soil foundations are mainly composed of sand particles, which usually present a single-grain structure. There is almost no cohesion between the particles, and the stability is mainly maintained by the friction between the particles. For example, under the action of wind or water flow, sand particles can move relatively freely, which makes the structure of the sandy soil foundation relatively loose. In many engineering construction scenarios, it is often necessary to quickly lay temporary roads on sandy soil foundations. Traditional temporary roads on sandy soil foundations are mainly simple compaction and leveling of sandy soil. This type of road has many problems in carrying vehicles:
[0003] First, the sand itself has a loose particle structure and low cohesion, which makes it easy to deform under vehicle loads;
[0004] Secondly, the sandy soil foundation has weak anti-scouring ability. When encountering rainfall or other water sources, the sandy soil can be easily washed away by the water flow, causing damage to the road structure.
[0005] Based on this, the present invention provides a method for paving a temporary road for traffic on a sandy foundation based on a high-strength polyethylene material to solve the above-mentioned technical problems. Summary of the invention
[0006] The purpose of the present invention is to provide a method for paving a temporary road open to traffic on a sandy foundation based on a high-strength polyethylene material. The prepared polyethylene board not only has good mechanical properties, but also has excellent wear resistance and light resistance, effectively ensuring its quality. The provided method for paving a temporary road open to traffic on a sandy foundation based on a high-strength polyethylene material is used for paving temporary roads and has a broader market prospect.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for paving a temporary road for traffic on a sandy soil foundation based on a high-strength polyethylene material, comprising the following steps:
[0009] S1. Prepare a high-strength polyethylene sheet, wherein the high-strength polyethylene sheet is composed of the following raw materials in parts by weight: 30 to 40 parts of linear polyethylene, 8 to 12 parts of random polypropylene, 3 to 6 parts of functional additives, 3 to 5 parts of synergistic additives, 2 to 4 parts of 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and 2 to 5 parts of antioxidants;
[0010] The preparation process of the high-strength polyethylene sheet is as follows:
[0011] Accurately weigh linear polyethylene, random polypropylene, functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidant and set aside;
[0012] Linear polyethylene and random polypropylene are mixed and heated to a molten state, and then functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidants are added thereto, stirred and mixed, and put into a flat vulcanizer for sheeting to obtain a high-strength polyethylene sheet;
[0013] S2. Use a vibratory roller to statically press the sand foundation 1 to 2 times, and then perform vibration compaction, and the compaction thickness of each layer of sand foundation is controlled at 20 to 30 cm;
[0014] S3. Driving steel pipes into the sandy foundation for reinforcement;
[0015] S4. Use measuring instruments to measure the flatness of the sand foundation surface and use a land grader to trim it;
[0016] S5. According to the road design requirements, set appropriate transverse and longitudinal slopes, and then lay high-strength polyethylene sheets on the surface of the sand foundation.
[0017] The present invention is further configured as follows: in step S1, the preparation process of the functional additive is as follows:
[0018] The glass fiber is put into the composite acid at a dosage ratio of 0.02 to 0.08 g / mL, treated at 60 to 66° C. for 240 to 260 min, filtered, washed with deionized water for 2 to 4 times, and then dried at 60 to 70° C. to constant weight to obtain the pretreated glass fiber;
[0019] Adding silicon dioxide into the modification liquid at a dosage ratio of 0.12 to 0.22 g / mL for ultrasonic treatment for 70 to 80 minutes, then treating at 80 to 85° C. for 200 to 220 minutes, filtering, washing with anhydrous ethanol and deionized water for 2 to 4 times, respectively, and then drying at 60 to 70° C. to constant weight to obtain pretreated silicon dioxide;
[0020] The pretreated silica is added into N,N-dimethylformamide at a dosage ratio of 0.01-0.03 g / mL and ultrasonically treated for 5-10 minutes, the pretreated glass fiber is added thereto, the ultrasonic treatment is continued for 60-70 minutes, and the treatment is carried out at 102-106° C. for 6-8 hours. After filtration, the pretreated silica is washed with anhydrous ethanol and deionized water for 2-6 times respectively, and then dried at 60-70° C. to constant weight to obtain a functional additive.
[0021] The present invention is further configured as follows: the composite acid is formed by mixing concentrated sulfuric acid with a mass concentration of 98% and concentrated nitric acid with a mass concentration of 68% in a volume ratio of 1:1.
[0022] The present invention is further configured as follows: the modified liquid is prepared by mixing anhydrous ethanol, γ-aminopropyltriethoxysilane and deionized water in a volume ratio of 10 to 8:3 to 2:1.
[0023] The present invention is further configured as follows: the addition amount of the pretreated glass fiber is 110-120% of the mass of the pretreated silicon dioxide.
[0024] The present invention is further configured as follows: in step S1, the preparation process of the synergist is as follows:
[0025] Add dolomite powder in a dosage ratio of 0.06-0.16 g / mL into deionized water, treat at 90-100° C. and 40-80 r / min for 10-15 min, and let stand for 50-60 min to obtain a pre-mixed material;
[0026] Silicon nitride, polyethylene glycol phosphate and pre-mixed materials are treated at a mass ratio of 0.02-0.05:0.07-0.12:1 at 52-62°C and 120-220 r / min for 40-50 minutes;
[0027] Then, the mixture is treated at 50-55° C. in a mixed gas atmosphere for 40-50 minutes, filtered, washed with deionized water for 2-4 times, and then dried at 60-70° C. to a constant weight to obtain a synergistic aid.
[0028] The present invention is further configured as follows: the mixed gas is formed by mixing carbon dioxide and nitrogen in a volume ratio of 2.1 to 2.3:1.
[0029] The present invention is further configured as follows: in the step S1, the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
[0030] The present invention is further configured as follows: in step S3, the length of the steel pipe is 1 to 2 m, and the spacing is 0.5 to 1 m.
[0031] The present invention is further configured as follows: in the step S5, it also includes fixing and connecting the laid high-strength polyethylene boards.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] In the present invention, a vibratory roller is used to statically press the sand foundation, and then vibrate and compact it, and a steel pipe is driven into the sand foundation for reinforcement, a measuring instrument is used to measure the flatness of the sand foundation surface, and a grader is used for trimming. According to the road design requirements, appropriate transverse slopes and longitudinal slopes are set, and then high-strength polyethylene sheets are laid on the surface of the sand foundation, wherein the high-strength polyethylene sheets are prepared with linear polyethylene, random polypropylene, functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidants as raw materials. The polyethylene sheet prepared by the present invention not only has good mechanical properties, but also has excellent wear resistance and light resistance, which effectively guarantees its quality. The method for laying temporary roads for traffic on sand foundations based on high-strength polyethylene materials provided by the present invention is used for laying temporary roads, has a broader market prospect, and is more suitable for promotion. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for paving a temporary road for traffic on a sandy foundation based on a high-strength polyethylene material, comprising the following steps:
[0037] S1. Prepare a high-strength polyethylene sheet, wherein the high-strength polyethylene sheet is composed of the following raw materials in parts by weight: 30 parts of linear polyethylene, 8 parts of random polypropylene, 3 parts of functional additives, 3 parts of synergistic additives, 2 parts of 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and 2 parts of antioxidant.
[0038] The preparation process of the functional additive is as follows:
[0039] The glass fiber was placed in the composite acid at a dosage ratio of 0.02 g / mL, treated at 60° C. for 240 min, filtered, washed twice with deionized water, and then dried at 60° C. to constant weight to obtain pretreated glass fiber;
[0040] The silica was added into the modified solution at a dosage ratio of 0.12 g / mL and ultrasonically treated for 70 min, then treated at 80°C for 200 min, filtered, washed twice with anhydrous ethanol and deionized water, and then dried at 60°C to constant weight to obtain pretreated silica;
[0041] The pretreated silica was added into N,N-dimethylformamide at a dosage ratio of 0.01 g / mL and ultrasonically treated for 5 minutes. The pretreated glass fiber was added thereto and ultrasonically treated for 60 minutes. The pretreated glass fiber was treated at 102°C for 6 hours. After filtration, the pretreated silica was washed twice with anhydrous ethanol and deionized water respectively, and then dried at 60°C to constant weight to obtain a functional additive.
[0042] Furthermore, the composite acid is prepared by mixing concentrated sulfuric acid with a mass concentration of 98% and concentrated nitric acid with a mass concentration of 68% in a volume ratio of 1:1.
[0043] The modified liquid is composed of anhydrous ethanol, γ-aminopropyltriethoxysilane and deionized water in a ratio of 1:1. 0 :3:1 volume ratio.
[0044] Furthermore, the amount of the pretreated glass fiber added is 110% of the mass of the pretreated silica.
[0045] In addition, the preparation process of the synergist is as follows:
[0046] Dolomite powder was added into deionized water at a dosage ratio of 0.06 g / mL, treated at 90°C and 40 r / min for 10 min, and allowed to stand for 50 min to obtain a pre-mixed material;
[0047] Silicon nitride, polyethylene glycol phosphate and pre-mixed materials were treated at a mass ratio of 0.02:0.07:1 at 52°C and 120 r / min for 40 min;
[0048] Then, the mixture was treated at 50° C. in a mixed gas atmosphere for 40 minutes, filtered, washed twice with deionized water, and then dried at 60° C. to constant weight to obtain a synergistic aid.
[0049] Furthermore, the mixed gas is formed by mixing carbon dioxide and nitrogen in a volume ratio of 2.1:1.
[0050] Among them, antioxidant 1010 is selected as the antioxidant.
[0051] In addition, the preparation process of high-strength polyethylene sheet is as follows:
[0052] Accurately weigh linear polyethylene, random polypropylene, functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidant and set aside;
[0053] Linear polyethylene and random polypropylene are mixed and heated to a molten state, and then functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidants are added thereto, stirred and mixed, and placed in a flat vulcanizer for sheeting to obtain a high-strength polyethylene sheet.
[0054] In this embodiment, it should be noted that silicon dioxide was purchased from Jinan Xinguan Chemical Products Co., Ltd., glass fiber was purchased from Tai'an Haosong Fiber Co., Ltd., dolomite powder was purchased from Hubei Tiancheng Nanomaterials Co., Ltd., linear polyethylene was purchased from Suzhou Xindezhi New Materials Co., Ltd., random polypropylene was purchased from Suzhou Yitianli Plastic Co., Ltd., and silicon nitride was purchased from Qinghe County Xingxin New Materials Technology Co., Ltd.
[0055] S2. Use a vibratory roller to statically compact the sand foundation once, and then perform vibration compaction. The compaction thickness of each layer of sand foundation is controlled at 20 cm.
[0056] S3. Drive steel pipes into the sandy foundation for reinforcement.
[0057] Among them, the length of the steel pipe is 1m and the spacing is 0.5m.
[0058] S4. Use measuring instruments to measure the flatness of the sand foundation surface and use a grader to trim it.
[0059] S5. According to the road design requirements, set appropriate transverse and longitudinal slopes, and then lay high-strength polyethylene sheets on the surface of the sand foundation.
[0060] In addition, it also includes fixing and connecting the laid high-strength polyethylene plates.
[0061] Example 2
[0062] This embodiment provides a method for paving a temporary road for traffic on a sandy foundation based on a high-strength polyethylene material, comprising the following steps:
[0063] S1. Prepare a high-strength polyethylene sheet, wherein the high-strength polyethylene sheet is composed of the following raw materials in parts by weight: 35 parts of linear polyethylene, 10 parts of random polypropylene, 4 parts of functional additives, 4 parts of synergistic additives, 3 parts of 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and 4 parts of antioxidants.
[0064] The preparation process of the functional additive is as follows:
[0065] The glass fiber was placed in the composite acid at a dosage ratio of 0.05 g / mL, treated at 63° C. for 250 min, filtered, washed with deionized water for 3 times, and then dried at 65° C. to constant weight to obtain the pretreated glass fiber;
[0066] The silica was added into the modified solution at a dosage ratio of 0.17 g / mL and ultrasonically treated for 75 min, then treated at 82°C for 210 min, filtered, washed with anhydrous ethanol and deionized water for 3 times, and then dried at 65°C to constant weight to obtain pretreated silica;
[0067] The pretreated silica was added into N,N-dimethylformamide at a dosage ratio of 0.02 g / mL and ultrasonically treated for 7 minutes. The pretreated glass fiber was added thereto and ultrasonically treated for 65 minutes. The pretreated silica was treated at 104°C for 7 hours. After filtration, the pretreated silica was washed with anhydrous ethanol and deionized water for 4 times respectively, and then dried at 65°C to constant weight to obtain a functional additive.
[0068] Furthermore, the composite acid is prepared by mixing concentrated sulfuric acid with a mass concentration of 98% and concentrated nitric acid with a mass concentration of 68% in a volume ratio of 1:1.
[0069] The modified liquid is composed of anhydrous ethanol, γ-aminopropyltriethoxysilane and deionized water. 9 :3:1 volume ratio.
[0070] Furthermore, the amount of pretreated glass fiber added is 110-120% of the mass of pretreated silica.
[0071] In addition, the preparation process of the synergist is as follows:
[0072] Dolomite powder was added into deionized water at a dosage ratio of 0.11 g / mL, treated at 95°C and 60 r / min for 12 min, and allowed to stand for 55 min to obtain a pre-mixed material;
[0073] Silicon nitride, polyethylene glycol phosphate and pre-mixed materials were treated at a mass ratio of 0.03:0.09:1 at 57°C and 170 r / min for 45 min;
[0074] Then, the mixture was treated at 52° C. in a mixed gas atmosphere for 45 minutes, filtered, washed with deionized water for three times, and then dried at 65° C. to a constant weight to obtain a synergistic aid.
[0075] Furthermore, the mixed gas is formed by mixing carbon dioxide and nitrogen in a volume ratio of 2.2:1.
[0076] Among them, antioxidant 1076 is selected as the antioxidant.
[0077] In addition, the preparation process of high-strength polyethylene sheet is as follows:
[0078] Accurately weigh linear polyethylene, random polypropylene, functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidant and set aside;
[0079] Linear polyethylene and random polypropylene are mixed and heated to a molten state, and then functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidants are added thereto, stirred and mixed, and placed in a flat vulcanizer for sheeting to obtain a high-strength polyethylene sheet.
[0080] In this embodiment, it should be noted that silicon dioxide was purchased from Jinan Xinguan Chemical Products Co., Ltd., glass fiber was purchased from Tai'an Haosong Fiber Co., Ltd., dolomite powder was purchased from Hubei Tiancheng Nanomaterials Co., Ltd., linear polyethylene was purchased from Suzhou Xindezhi New Materials Co., Ltd., random polypropylene was purchased from Suzhou Yitianli Plastic Co., Ltd., and silicon nitride was purchased from Qinghe County Xingxin New Materials Technology Co., Ltd.
[0081] S2. Use a vibratory roller to statically compact the sand foundation twice, and then perform vibration compaction. The compaction thickness of each layer of sand foundation is controlled at 25 cm.
[0082] S3. Drive steel pipes into the sandy foundation for reinforcement.
[0083] Among them, the length of the steel pipe is 2m and the spacing is 0.7m.
[0084] S4. Use measuring instruments to measure the flatness of the sand foundation surface and use a grader to trim it.
[0085] S5. According to the road design requirements, set appropriate transverse and longitudinal slopes, and then lay high-strength polyethylene sheets on the surface of the sand foundation.
[0086] In addition, it also includes fixing and connecting the laid high-strength polyethylene plates.
[0087] Example 3
[0088] This embodiment provides a method for paving a temporary road for traffic on a sandy foundation based on a high-strength polyethylene material, comprising the following steps:
[0089] S1. Prepare a high-strength polyethylene sheet, wherein the high-strength polyethylene sheet is composed of the following raw materials in parts by weight: 40 parts of linear polyethylene, 12 parts of random polypropylene, 6 parts of functional additives, 5 parts of synergistic additives, 4 parts of 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and 5 parts of antioxidant.
[0090] The preparation process of the functional additive is as follows:
[0091] The glass fiber was placed in the composite acid at a dosage ratio of 0.08 g / mL, treated at 66° C. for 260 min, filtered, washed with deionized water for 4 times, and then dried at 70° C. to constant weight to obtain pretreated glass fiber;
[0092] The silica was added into the modified solution at a dosage ratio of 0.22 g / mL and ultrasonically treated for 80 min, then treated at 85°C for 220 min, filtered, washed with anhydrous ethanol and deionized water for 4 times, and then dried at 70°C to constant weight to obtain pretreated silica;
[0093] The pretreated silica was added into N,N-dimethylformamide at a dosage ratio of 0.03 g / mL and ultrasonically treated for 10 minutes. The pretreated glass fiber was added thereto and ultrasonically treated for 70 minutes. The pretreated glass fiber was treated at 106°C for 8 hours. After filtration, the pretreated silica was washed with anhydrous ethanol and deionized water for 6 times respectively, and then dried at 70°C to constant weight to obtain a functional additive.
[0094] Furthermore, the composite acid is prepared by mixing concentrated sulfuric acid with a mass concentration of 98% and concentrated nitric acid with a mass concentration of 68% in a volume ratio of 1:1.
[0095] The modified liquid is prepared by mixing anhydrous ethanol, gamma-aminopropyltriethoxysilane and deionized water in a volume ratio of 10-8:3-2:1.
[0096] Furthermore, the amount of pretreated glass fiber added is 120% of the mass of pretreated silica.
[0097] In addition, the preparation process of the synergist is as follows:
[0098] Dolomite powder was added into deionized water at a dosage ratio of 0.16 g / mL, treated at 100°C and 80 r / min for 15 min, and allowed to stand for 60 min to obtain a pre-mixed material;
[0099] Silicon nitride, polyethylene glycol phosphate and pre-mixed materials were treated at a mass ratio of 0.05:0.12:1 at 62°C and 220 r / min for 50 min;
[0100] Then, the mixture was treated at 55° C. in a mixed gas atmosphere for 50 minutes, filtered, washed with deionized water for 4 times, and then dried at 70° C. to a constant weight to obtain a synergistic aid.
[0101] Furthermore, the mixed gas is formed by mixing carbon dioxide and nitrogen in a volume ratio of 2.3:1.
[0102] Among them, the antioxidant is antioxidant CA.
[0103] In addition, the preparation process of high-strength polyethylene sheet is as follows:
[0104] Accurately weigh linear polyethylene, random polypropylene, functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidant and set aside;
[0105] Linear polyethylene and random polypropylene are mixed and heated to a molten state, and then functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidants are added thereto, stirred and mixed, and placed in a flat vulcanizer for sheeting to obtain a high-strength polyethylene sheet.
[0106] In this embodiment, it should be noted that silicon dioxide was purchased from Jinan Xinguan Chemical Products Co., Ltd., glass fiber was purchased from Tai'an Haosong Fiber Co., Ltd., dolomite powder was purchased from Hubei Tiancheng Nanomaterials Co., Ltd., linear polyethylene was purchased from Suzhou Xindezhi New Materials Co., Ltd., random polypropylene was purchased from Suzhou Yitianli Plastic Co., Ltd., and silicon nitride was purchased from Qinghe County Xingxin New Materials Technology Co., Ltd.
[0107] S2. Use a vibratory roller to statically compact the sand foundation twice, and then perform vibration compaction. The compaction thickness of each layer of sand foundation should be controlled at 20 to 30 cm.
[0108] S3. Drive steel pipes into the sandy foundation for reinforcement.
[0109] Among them, the length of the steel pipe is 2m and the spacing is 1m.
[0110] S4. Use measuring instruments to measure the flatness of the sand foundation surface and use a grader to trim it.
[0111] S5. According to the road design requirements, set appropriate transverse and longitudinal slopes, and then lay high-strength polyethylene sheets on the surface of the sand foundation.
[0112] In addition, it also includes fixing and connecting the laid high-strength polyethylene plates.
[0113] Comparative Example 1: The difference from Example 1 is that an equal amount of glass fiber is used to replace the functional additive in this example.
[0114] Comparative Example 2: The difference from Example 1 is that in this example, an equal amount of dolomite powder is used to replace the synergistic aid.
[0115] Performance test: The high-strength polyethylene sheet samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the high-strength polyethylene sheets provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:
[0116] 1. Mechanical test: The test method is to perform bending strength test according to GB / T9341-2008 and tensile strength test according to GB / T 1040.2-2022.
[0117] 2. Wear resistance test: The test method is GB / T3960-2016.
[0118] 3. Light resistance test: The test method is GB / T16422.2-2022.
[0119] The obtained test data are recorded in Tables 1 to 3 below:
[0120] Table 1 Mechanical properties test results of each group of polyethylene sheets
[0121] Group Bending strength(MPa) Tensile strength(MPa) Example 1 Group 42.5 37.3 Example 2 Group 42.2 37.1 Example 3 Group 42.3 37.1 Comparison group 1 29.8 23.9 Comparison of 2 groups 33.5 30.4
[0122] Table 2 Wear resistance test results of each group of polyethylene sheets
[0123]
[0124]
[0125] Table 3 Light resistance test results of each group of polyethylene sheets
[0126] Group Light resistance level Example 1 Group Level 5 Example 2 Group Level 5 Example 3 Group Level 5 Comparison group 1 Level 4 Comparison of 2 groups Level 3
[0127] By comparing and analyzing the relevant data in Tables 1 to 3, it can be seen that the polyethylene sheet prepared by the present invention not only has good mechanical properties, but also has excellent wear resistance and light resistance, which effectively guarantees its quality. This shows that the method for laying a temporary road on a sandy foundation based on a high-strength polyethylene material provided by the present invention is used for laying temporary roads, has a broader market prospect, and is more suitable for promotion.
[0128] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0129] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material, characterized in that: The following steps are involved: S1. Prepare a high-strength polyethylene sheet, wherein the high-strength polyethylene sheet is composed of the following raw materials in parts by weight: 30 to 40 parts of linear polyethylene, 8 to 12 parts of random polypropylene, 3 to 6 parts of functional additives, 3 to 5 parts of synergistic additives, 2 to 4 parts of 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and 2 to 5 parts of antioxidants; The preparation process of the high-strength polyethylene sheet is as follows: Accurately weigh linear polyethylene, random polypropylene, functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidant and set aside; Linear polyethylene and random polypropylene are mixed and heated to a molten state, and then functional additives, synergistic additives, 1,3:2,4-di(3,4-dimethylbenzylidene)-D-sorbitol and antioxidants are added thereto, stirred and mixed, and put into a flat vulcanizer for sheeting to obtain a high-strength polyethylene sheet; S2. Use a vibratory roller to statically press the sand foundation 1 to 2 times, and then perform vibration compaction, and the compaction thickness of each layer of sand foundation is controlled at 20 to 30 cm; S3. Driving steel pipes into the sandy foundation for reinforcement; S4. Use measuring instruments to measure the flatness of the sand foundation surface and use a land grader to trim it; S5. According to the road design requirements, set appropriate transverse and longitudinal slopes, and then lay high-strength polyethylene sheets on the surface of the sand foundation.
2. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 1, characterized in that: In step S1, the preparation process of the functional additive is as follows: The glass fiber is put into the composite acid at a dosage ratio of 0.02 to 0.08 g / mL, treated at 60 to 66° C. for 240 to 260 min, filtered, washed with deionized water for 2 to 4 times, and then dried at 60 to 70° C. to constant weight to obtain the pretreated glass fiber; Adding silicon dioxide into the modification liquid at a dosage ratio of 0.12 to 0.22 g / mL for ultrasonic treatment for 70 to 80 minutes, then treating at 80 to 85° C. for 200 to 220 minutes, filtering, washing with anhydrous ethanol and deionized water for 2 to 4 times, respectively, and then drying at 60 to 70° C. to constant weight to obtain pretreated silicon dioxide; The pretreated silica is added into N,N-dimethylformamide at a dosage ratio of 0.01-0.03 g / mL and ultrasonically treated for 5-10 minutes, the pretreated glass fiber is added thereto, the ultrasonic treatment is continued for 60-70 minutes, and the treatment is carried out at 102-106° C. for 6-8 hours. After filtration, the pretreated silica is washed with anhydrous ethanol and deionized water for 2-6 times respectively, and then dried at 60-70° C. to constant weight to obtain a functional additive.
3. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 2, characterized in that: The composite acid is prepared by mixing concentrated sulfuric acid with a mass concentration of 98% and concentrated nitric acid with a mass concentration of 68% in a volume ratio of 1:
1.
4. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 2, characterized in that: The modified liquid is prepared by mixing anhydrous ethanol, gamma-aminopropyltriethoxysilane and deionized water in a volume ratio of 10-8:3-2:
1.
5. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 2, characterized in that: The addition amount of the pretreated glass fiber is 110-120% of the mass of the pretreated silicon dioxide.
6. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 1, characterized in that: In step S1, the preparation process of the synergist is as follows: Add dolomite powder in a dosage ratio of 0.06-0.16 g / mL into deionized water, treat at 90-100° C. and 40-80 r / min for 10-15 min, and let stand for 50-60 min to obtain a pre-mixed material; Silicon nitride, polyethylene glycol phosphate and pre-mixed materials are treated at a mass ratio of 0.02-0.05:0.07-0.12:1 at 52-62°C and 120-220 r / min for 40-50 minutes; Then, the mixture is treated at 50-55° C. in a mixed gas atmosphere for 40-50 minutes, filtered, washed with deionized water for 2-4 times, and then dried at 60-70° C. to a constant weight to obtain a synergistic aid.
7. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 6, characterized in that: The mixed gas is formed by mixing carbon dioxide and nitrogen in a volume ratio of 2.1 to 2.3:
1.
8. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 1, characterized in that: In the step S1, the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
9. The method for laying a temporary road for traffic on a sandy foundation based on high-strength polyethylene material according to claim 1, characterized in that: In step S3, the length of the steel pipes is 1 to 2 m, and the spacing is 0.5 to 1 m.
10. The method for laying a temporary road on a sandy foundation based on high-strength polyethylene material according to claim 1, characterized in that: In the step S5, the process also includes fixing and connecting the laid high-strength polyethylene plates.
Citation Information
Cited By
Tailing mechanical mining transportation road underlying device and method
CN120486196A